LEGAL PROTECTION CREDITOR OF DEFAULT DEBTORS IN UNSECURED LOANS IN TERMS OF LAW NO.8 OF 1999 CONCERNING CONSUMER PROTECTION - Andi Aan Hastaman; Ma’ruf Hafidz; Hasbuddin Khalid (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal